Analisis Prosedur Pengelolaan Arsip Dinamis Pada Kantor Sub Bagian Keuangan Dinas Kehutanan - Hafri Deliani; Armiati Armiati (Universitas Negeri Padang, 2021)
This study aims to oversee the management of dynamic records, human resources who carry out archive management activities to monitor obstacles in managing archives at the Sub-Division of Finance Office of the Forestry Service of West Sumatra Province. This research method is descriptive qualitative, with data sources of several informants who are determined based on criteria in accordance with interviews and direct observations to the object of research. Secondary data that supports this research is obtained from documents available at the place of research object. Based on the information from the information, this research can serve that the management of dynamic archives as a whole is almost done well, but it is still not maximized. This is because: 1) based on incoming and outgoing mails, it has not been implemented optimally; 2) the use of dynamic archives has not been implemented properly and archive recovery still takes a long time; 3) archive maintenance has not been implemented optimally; 4) shrinkage archives that are not in accordance with existing procedures. This happens because of several reasons: 1) there is no archivist or special employee who manages the records; 2) Inadequate quality and quantity of archiving facilities. Based on the research above, archives can be provided to employees to increase awareness of dynamic management. The leadership should place human resources who manage archives who have an archivist background, provide adequate and complete facilities and infrastructure.Keywords : dynamic archive management, archive dynamic.